MICHELIA CHAMPACA MITIGATES NOISE STRESS-INDUCED OXIDATIVE AND BEHAVIORAL ALTERATIONS IN RAT BRAIN REGIONS - MALATHI S; HM, VIDYASHREE; RAVINDRAN RAJAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Noise is a globally prevalent environmental stressor known to contribute to a range of psychophysiological issues, including auditory defects and non-auditory disorders. The brain plays a central role in recognizing, interpreting, and responding to such stressors. The objective of the present study was to evaluate the anxiolytic, neuroprotective, and antioxidant effects of Michelia champaca in rats with noise-induced stress. Methods: Animals were exposed to noise stress (100 dB for 4 h/day) for 1 day and 30 days, after which endogenous free radical levels and antioxidant activities were assessed in discrete brain regions. Results: It demonstrated that noise exposure significantly (p<0.05) elevated free radical production and disrupted antioxidant status across various brain regions. Noise exposure also affected membrane bound enzymes. A marked decrease (p<0.05) was observed in the activities of Ca2⁺-ATPase, Mg2⁺-ATPase, and Na⁺/K⁺-ATPase. Behavioral assessments showed that noise exposed rats exhibited increased anxiety-like behaviors compared to controls. However, treatment with M. champaca (400 mg/kg body weight) effectively (p<0.05) mitigated these effects. The plant extract reduced free radical levels, restored antioxidant enzyme activities, and normalized the functions of membrane-bound enzymes, bringing them closer to control levels. Conclusion: The findings suggest that M. champaca possesses potent free radical scavenging and antioxidant properties, likely due to its phytochemical constituents. These properties contribute to its therapeutic potential in alleviating biochemical and behavioral abnormalities induced by noise stress.